Strategic Interventions of Zakat Institution in Empowering MSEs: The Case of BAZNAS in Bone Regency - Ramli, Ahmad Faidh Annur; Jaenudin; Yuniarti, Vinna Sri; Idfilandu, Syena; Hidayat, Agi Attaubah (Milkiyah: Jurnal Hukum Ekonomi Syariah, 2025)
Productive zakat is an important part of Islamic social finance that aims to help reduce poverty by supporting micro and small businesses. Unlike traditional charity, productive zakat gives business capital to help zakat recipients (Mustahik) become independent. In Indonesia, especially in rural areas, this type of support plays a key role in improving people’s economic conditions. This study focuses on how a zakat institution attempts to help micro and small businesses through its productive zakat programmes. The research employed a qualitative method using a case study approach conducted at BAZNAS in Bone Regency, Indonesia. Data were collected through interviews and field observation involving BAZNAS staff, Mustahik, and leaders of local MSEs, and related document review. The results show that the mentoring provided is mostly limited to short verbal guidance when the funds are first given. There are no structured trainings and regular follow-ups. These issues are compounded by a lack of staff, long distances between locations, and no clear way to measure progress. However, we find that there are also chances to improve the programme, such as the use of digital tools, building partnerships, and strengthening local MSE organisations. This study demonstrates that mentoring needs to be more measurable so that productive zakat truly helps people become economically independent. We also offer insights from this study for improving zakat programmes in other rural areas